Association of an ERAP1 ERAP2 haplotype with familial ankylosing spondylitis. Issue 4 (10th May 2009) - Tsui, Florence W L; Haroon, Nigil; Reveille, John D; Rahman, Proton; Chiu, Basil; Tsui, Hing Wo; Inman, Robert D
Abstract : Objectives: To assess whether there is excess transmission of alleles from the ERAP1 ERAP2 locus in families with ankylosing spondylitis (AS). Methods: 199 multiplex families with AS with four non-synonymous single nucleotide polymorphisms (SNPs), three in the endoplasmic reticulum aminopeptidase 1 ( ERAP1 ) gene ( rs27044, rs10050860 and rs30187 ) and one in the endoplasmic reticulum aminopeptidase 2 ( ERAP2 ) gene ( rs2549782 ), were genotyped and family-based association analyses were performed. Results: Family-based association testing (FBAT –e; empirical variance option) analysis showed that ERAP1 rs30187[T] was associated with AS (additive model: p = 0.02; dominant model: p=0.007). Haplotype permutation tests (HBAT-p) showed that a haplotype in the ERAP1 and ERAP2 locus ( rs27044[G] rs30187[T] rs2549782[T] ) was significantly associated with AS (two-sided p value by permutation test 0.009 for additive and 0.008 for dominant model, respectively). Conclusion: This study shows that one ERAP1 SNP and a haplotype in the ERAP1 and ERAP2 locus are associated with familial AS.